2020
DOI: 10.1155/2020/5846938
|View full text |Cite
|
Sign up to set email alerts
|

Galangin Inhibits Cholangiocarcinoma Cell Growth and Metastasis through Downregulation of MicroRNA-21 Expression

Abstract: Galangin, a natural flavonoid product derived from the root of galangal, is emerging as a promising anticancer agent against multiple cancers. Yet, whether it also has antitumor effects on cholangiocarcinoma (CCA) and the underlying mechanism is still unknown. Herein, we demonstrate that galangin exhibits multiple antitumor effects on CCA cells including decreases cell viability; inhibits proliferation, migration, and invasion; and induces apoptosis. Moreover, those phenotypic changes are associated with downr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…MiR-21 is well recognized as an oncomir, which is highly expressed in cholangiocarcinoma tissue compared with the noncancerous biliary epithelium [ 24 , 25 , 26 , 27 ]. It plays important roles in the progress of cholangiocarcinoma through targeting PTEN/AKT pathway [ 27 , 28 ], TIMP3 (tissue inhibitor of metalloproteinases 3) [ 29 ], 15-PGDH (15-hydroxyprostaglandin dehydrogenase) [ 24 ], or EMT (epithelial–mesenchymal transition) [ 30 ]. We found that higher plasma miR-21 level was significantly associated with larger tumor size, implying a close correlation between miR-21 and tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-21 is well recognized as an oncomir, which is highly expressed in cholangiocarcinoma tissue compared with the noncancerous biliary epithelium [ 24 , 25 , 26 , 27 ]. It plays important roles in the progress of cholangiocarcinoma through targeting PTEN/AKT pathway [ 27 , 28 ], TIMP3 (tissue inhibitor of metalloproteinases 3) [ 29 ], 15-PGDH (15-hydroxyprostaglandin dehydrogenase) [ 24 ], or EMT (epithelial–mesenchymal transition) [ 30 ]. We found that higher plasma miR-21 level was significantly associated with larger tumor size, implying a close correlation between miR-21 and tumor proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Also, galangin has a protective effect on ulcerative colitis induced by dextran sulfate sodium in mice and rats (Sangaraju et al 2019 ; Fan et al 2021 ). Galangin inhibits cell growth and metastasis of cholangiocarcinoma by downregulating the expression of microRNA-21 (Zou et al 2020 ). Besides, galangin inhibits epithelial-mesenchymal transition and angiogenesis of glioma by downregulating CD44 (Chen et al 2019a ).…”
Section: Trpcs Antagonistsmentioning
confidence: 99%
“…As stated in Section 2.1.8 , miR-21 directly modulates PTEN, whose function is to inactivate PI3K/Akt signaling in cancer. As a consequence of the miR-21 inhibition, formononetin and galangin upregulate PTEN levels in bladder and cholangiocarcinoma, respectively, thereby inhibiting cancer aggressiveness [ 42 , 43 ]. In colorectal cancer, gambogic acid induces apoptosis by suppressing miR-21 expression, and the cytotoxicity of gambogic acid is reversed by overexpressing miR-21 [ 44 ].…”
Section: Oncogenic Mirnas Inhibited By Phytochemicals Currently Evmentioning
confidence: 99%
“…Matrine can facilitate cell cycle arrest and prohibit cell survival by enhancing miR-22 levels in colorectal cancer ( Figure 1 and Table 4 ). Indeed, it was also noticed that miR-22 targets Erb-B2 receptor tyrosine kinase 3 (ERBB3) and MDS1 and EVI1 complex locus (MECOM) in colorectal cancer [ 43 ]. However, given that miR-22 can target various transcripts with different functions, it is unsurprising that miR-22 acts as either an oncogene or tumor suppressor in a cellular context-dependent manner [ 222 ].…”
Section: Tumor-suppressive Mirnas Induced By Phytochemicals Currenmentioning
confidence: 99%